A diastereoselective approach to axially chiral biaryls via electrochemically enabled cyclization cascade - Yan, Hong; Mao, Zhong-Yi; Hou, Zhong-Wei; Song, Jinshuai; Xu, Hai-Chao (Beilstein Journal of Organic Chemistry, 2019)
A diastereoselective approach to axially chiral imidazopyridine-containing biaryls has been developed. The reactions proceed through a radical cyclization cascade to construct the biaryls with good to excellent central-to-axial chirality transfer.
Keywords: axial chirality; biaryl; electrochemistry; oxidation; radical

(untitled) - Bringmann, G.; Gulder, T.; Gulder, T. A. M.; Breuning, M. (Chem. Rev., 2011)

(untitled) - Pu, L. (Chem. Rev., 1998)

(untitled) - Tanaka, K. (Chem. – Asian J., 2009)

(untitled) - Wallace, T. W. (Org. Biomol. Chem., 2006)

(untitled) - Bringmann, G.; Price Mortimer, A. J.; Keller, P. A.; Gresser, M. J.; Garner, J.; Breuning, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Ma, G.; Sibi, M. P. (Chem. – Eur. J., 2015)

(untitled) - Link, A.; Sparr, C. (Chem. Soc. Rev., 2018)

(untitled) - Wang, Y.-B.; Tan, B. (Acc. Chem. Res., 2018)

(untitled) - Yang, H.; Yang, X.; Tang, W. (Tetrahedron, 2016)

(untitled) - Wencel-Delord, J.; Panossian, A.; Leroux, F. R.; Colobert, F. (Chem. Soc. Rev., 2015)

(untitled) - Raut, V. S.; Jean, M.; Vanthuyne, N.; Roussel, C.; Constantieux, T.; Bressy, C.; Bugaut, X.; Bonne, D.; Rodriguez, J. (J. Am. Chem. Soc., 2017)

(untitled) - Vorogushin, A. V.; Wulff, W. D.; Hansen, H.-J. (J. Am. Chem. Soc., 2002)

(untitled) - Guo, F.; Konkol, L. C.; Thomson, R. J. (J. Am. Chem. Soc., 2011)

(untitled) - Qiu, L.; Kwong, F. Y.; Wu, J.; Lam, W. H.; Chan, S.; Yu, W.-Y.; Li, Y.-M.; Guo, R.; Zhou, Z.; Chan, A. S. C. (J. Am. Chem. Soc., 2006)

(untitled) - Kärkäs, M. D. (Chem. Soc. Rev., 2018)

(untitled) - Zhao, Y.; Xia, W. (Chem. Soc. Rev., 2018)

(untitled) - Chen, J.-R.; Hu, X.-Q.; Lu, L.-Q.; Xiao, W.-J. (Chem. Soc. Rev., 2016)

(untitled) - Zard, S. Z. (Chem. Soc. Rev., 2008)

(untitled) - Xiong, T.; Zhang, Q. (Chem. Soc. Rev., 2016)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Chem. Rev., 2017)

(untitled) - Wiebe, A.; Gieshoff, T.; Möhle, S.; Rodrigo, E.; Zirbes, M.; Waldvogel, S. R. (Angew. Chem., Int. Ed., 2018)

(untitled) - Möhle, S.; Zirbes, M.; Rodrigo, E.; Gieshoff, T.; Wiebe, A.; Waldvogel, S. R. (Angew. Chem., Int. Ed., 2018)

(untitled) - Feng, R.; Smith, J. A.; Moeller, K. D. (Acc. Chem. Res., 2017)

(untitled) - Moeller, K. D. (Chem. Rev., 2018)

(untitled) - Yan, M.; Kawamata, Y.; Baran, P. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Yang, Q.-L.; Fang, P.; Mei, T.-S. (Chin. J. Chem., 2018)

(untitled) - Tang, S.; Liu, Y.; Lei, A. (Chem, 2018)

(untitled) - Yoshida, J.-i.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Jiang, Y.; Xu, K.; Zeng, C. (Chem. Rev., 2018)

(untitled) - Francke, R.; Little, R. D. (Chem. Soc. Rev., 2014)

(untitled) - Hou, Z.-W.; Mao, Z.-Y.; Melcamu, Y. Y.; Lu, X.; Xu, H.-C. (Angew. Chem., Int. Ed., 2018)

(untitled) - Hou, Z.-W.; Yan, H.; Song, J.-S.; Xu, H.-C. (Chin. J. Chem., 2018)

(untitled) - Hou, Z.-W.; Mao, Z.-Y.; Song, J.; Xu, H.-C. (ACS Catal., 2017)

(untitled) - Hou, Z.-W.; Mao, Z.-Y.; Zhao, H.-B.; Melcamu, Y. Y.; Lu, X.; Song, J.; Xu, H.-C. (Angew. Chem., Int. Ed., 2016)

(untitled) - Gieshoff, T.; Kehl, A.; Schollmeyer, D.; Moeller, K. D.; Waldvogel, S. R. (J. Am. Chem. Soc., 2017)

(untitled) - Xu, H.-C.; Moeller, K. D. (J. Am. Chem. Soc., 2008)

(untitled) - Gieshoff, T.; Schollmeyer, D.; Waldvogel, S. R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Kehl, A.; Breising, V. M.; Schollmeyer, D.; Waldvogel, S. R. (Chem. – Eur. J., 2018)

(untitled) - Lin, M.-Y.; Xu, K.; Jiang, Y.-Y.; Liu, Y.-G.; Sun, B.-G.; Zeng, C.-C. (Adv. Synth. Catal., 2018)

(untitled) - Zhang, S.; Li, L.; Xue, M.; Zhang, R.; Xu, K.; Zeng, C. (Org. Lett., 2018)

(untitled) - Hu, X.; Zhang, G.; Bu, F.; Nie, L.; Lei, A. (ACS Catal., 2018)

(untitled) - Seeman, J. I. (J. Chem. Educ., 1986)